(untitled) (Studia Prawnicze / The Legal Studies, 1981)
First of all the Author stresses the importance of numerous works of prof. S. Zawadzki, and particularity the studies devoted to the analysis of regularities of development of socialist democracy. Discussing the notion of socialist democracy the Author opposes it to bour- geois democracy, stressing the relation of socialist democracy with practical exercise of political power. While the bourgeois system guarantees only formal equality of the citizens, in the socialist system this equality is guaranteed by social ownership of means of production, and the essence of socialist democracy is collective, organized and conscious, creative activity of the working masses. Development of socialist democracy depends upon rational organization of the system of cooperation of its various forms - state and other than state. The fundamental element which initiates and guarantees this cooperation is the leading role of the workers’ party, fundamental political element of socialist democracy. Leading role of the working class and of its party is expressed in defining directions of democratic activity of the working masses and in realization in democratic way of objective regularities of social development. During the last years, scientific and technical revolution exerted meaningful influence on development of socialist democracy; it brought the increase of the level of education of the society in socialist countries. In the sphere of economy socialist democracy is realized in the process of all-national management and planification, and in the process of shaping socialist interpersonal relations in workplaces as well as the relations between particular workplaces. Socialist democracy, as it brings out all creative capabilities of the working masses, conditions theoretical motivation and the reality of particular stages of the planification process. It develops in the direction of wider making use of social discussion already in the stage preceding the decision-making. Modern uni-personal management in economy must be based on wide and fair collective consultation. Also as far as a given territorial unit is concerned, its problems must be solved by a common, coordinated effort of state and social forces (known as “territorial rationalization”). And at the same time, specific aims and objects of employing means and forces must be subjected to public discussion in organs of representation, in collectives of workers and in other organizations. Further development of socialist democracy will be promoted by scientificly developed contents, tasks and possibilities of various organizational forms of socialist democracy.